Flytande naturgas inom SECA - Existerar det en spotmarknad för LNG-drivna tankfartyg inom SECA? - Werner, Magnus; Ek, Viktor (My University, 2015)
The new rules for sulphur emissions from ships in North Sea and in the Baltic Sea that IMO (International Maritime Organization) implemented the first of January 2015, forced shipping companies to take actions to fulfil the new requirements. The Alternatives for ships within SECA is to either clean the emissions with a scrubber to reduce the Sulphur content in the emissions or to use fuels that contains maximum 0,1 percent Sulphur. LNG (Liquefied Natural Gas) has been an alternative for a very long time even if the shipping business has rejected it. What this case study examine is if it is possible to operate a LNG-driven tanker on the spot market. The questions in this report are addressed to ports and gas suppliers in SECA and also to Swedish tanker shipping companies. The result shows that it is possible to operate a LNG-driven tanker on the spot market if the ship has a duel fuel engine.
Keywords: Transport; Hållbar utveckling; Transportteknik och logistik; Transport; Sustainable Development; Transport Systems and Logistics